PENGARUH KOMPETENSI PERANGKAT DESA, TRANSPARANSI, PARTISIPASI MASYARAKAT DAN SISTEM PENGENDALIAN INTERNAL, TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Putri, Winitriwidia Jaya; Kusumawardani, Anisa (Jurnal Riset Akuntansi Politala, 2025)
This study aims to analyse the extent to which village government competence, transparency, community participation, and internal control systems affect the accountability of village fund management in Jelemuk Village. This research is expected to provide insight into the factors that support or hinder accountability in the management of Jelemuk village funds, so that it can be a recommendation for the village government in improving village financial governance more effectively and sustainably. The research sample was the Jelemuk village government related to the research variables, namely 68 questionnaire with primary data . Data analysis was carried out using the Multiple Linear Regression method with the SPSS 25 analysis tool. The results showed that Village Government Competence, Transparency and Internal Control System had an effect on Village Fund management accountability, while Community Participation had no effect on Village Fund Management Accountability.